the Effect of Electronic Word of Mouth on Instagram Social Media on Purchasing Decisions (Case Study on Second Snoop Bengkulu Customers) - Kiki Sanakri; Mimi Kurnia Nengsih (Penerbit Jurnal Indonesia, 2023)
The purpose of this study was to determine the effect of electronic word of mouth (E-Wom) dimensions on social media on purchasing decisions for customers at Second Snoop Bengkulu Stores. The research method used is quantitative, the population in this study is 100 employees, the total sample is the entire population, namely 100 consumers. Data collection techniques are through observation, questionnaires. The analysis technique used is the Multiple Linear Regression Test. The results of the research show that intensity has a positive effect on purchasing decisions for Second Snoop Bengkulu Store customers, this is evidenced from the hypothesis test with t-test obtained tcount > ttable (11,395> 1,699). Valence of Opinion (X2) has a positive effect on consumer purchasing decisions (Y) on Second Snoop Bengkulu Store Customers, this is proven from the hypothesis test with t-test obtained tcount > ttable (2.240> 1.699). Content (X2) has a positive effect on consumer purchasing decisions (Y) on Second Snoop Bengkulu Store Customers. This is evidenced from the hypothesis test with the t-test obtained tcount > ttable (4.376> 1.699). Intensity (X1), Valence of Opinion (X2), and Content (X3) affect consumer purchasing decisions (Y). This can be seen from the hypothesis test together (simultaneously) Ftable > Fcount (92,545 > 3,940). This is proven from the correlation analysis R = 0.802 (80.2%) and is close to 1. And the coefficient of determination is R2 = 0.743 or about 74.3% while 25.7% is a contribution of other variables not examined. Keywords: Intensity, Valence of Opinion, Content, Purchase decision